2016
DOI: 10.1108/sc-09-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Is volunteering for everyone? Volunteering opportunities for young ex-offenders

Abstract: offenders Structured abstractPurpose: The purpose of the study was to explore volunteering opportunities for young adults with criminal records ('young ex-offenders'). Design:The study was conducted primarily in one London borough. It involved mapping volunteering opportunities for young ex-offenders and conducting in-depth interviews with young ex-offenders and practitioners from volunteer-involving organisations and resettlement organisations. Value: This paper offers practical insight into the scope of volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Through the narratives, it can be viewed that the importance of money is not the most important aspect they may gain. This is similar to Kirby's (2016) research that found that young offenders taking part in employment very rarely spoke about the link between volunteering and gaining employment, rather they spoke highly of the softer skills they gained. It has been previously recognised that an accomplishment for ex-offenders, such as engaging in a programme, can lead to a sense of hope and an orientation towards the future (Richie, 2001).…”
Section: Looking To the Futuresupporting
confidence: 82%
“…Through the narratives, it can be viewed that the importance of money is not the most important aspect they may gain. This is similar to Kirby's (2016) research that found that young offenders taking part in employment very rarely spoke about the link between volunteering and gaining employment, rather they spoke highly of the softer skills they gained. It has been previously recognised that an accomplishment for ex-offenders, such as engaging in a programme, can lead to a sense of hope and an orientation towards the future (Richie, 2001).…”
Section: Looking To the Futuresupporting
confidence: 82%
“…The benefits of volunteering are closely linked to individuals' motivation to participate in this area of volunteering. Drawing comparisons with previous research from Kirby [6], this study elaborated on how individuals who volunteer are more likely to feel an increased sense of moral satisfaction and see an individual's happiness more than those who do not engage in volunteering. Volunteering increases physical and mental health, as well as integrating into society and feeling accepted by the wider community, which was highlighted as a key benefit to volunteers [57,58].…”
Section: Discussionmentioning
confidence: 98%
“…Working with youth to develop a sense of care and responsibility will undoubtedly and immensely help reap valuable fruits in the field of volunteerism [5]. Understanding their attitudes enhances or even solely determines the way to fruitfully energize youth, specifically students' involvement in volunteerism [6].…”
Section: Introductionmentioning
confidence: 99%